Missionary Thinking in the Perspective of Adult Education Principles and Bible Study - Harianto GP; Hana Suparti; Muner Daliman; Jonathan D. James (Jurnal Jaffray, 2022)
Adult education is formulated as a process that fosters a desire to ask questions and learn continuously throughout life. The study aims to answer the questions: What is the Bible as the basis for teaching design? What are the characteristics of adult education? What is the correct and effective formulation of a missionary for adult education? The answers are: 1) The Bible as the basis for teaching design means Bible values are the source and guide of all curricula; 2) Characteristics of adult education, both in the field of work and other experiences, are independent, think for their interests (future) and have diverse backgrounds; 3) Appropriate and effective missionary Bible studies for adult education are as follows: a) curriculum that reflects God's missionary vision (Missio Dei); b) a curriculum model for a missionary approach that uses information, stimulation, or projection and a learning process for missionary approach which is developed based on the interests of adults by integrating all forms of activities.